INVESTIGATING THE POTENTIAL OF AN ANTIDEPRESSANT INTRANASAL MUCOADHESIVE MICROEMULSION - Singh, Gurpreet; Rawat, Nisha; Singh, Kirti; Sarwal, Amita; Sinha, V. R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The main aim of this study was to formulate, develop and optimized a duloxetine hydrochloride (dlx-hcl) loaded mucoadhesive microemulsion intended for intranasal administration. Methods: Established on solubility studies capmul mcm, transcutol-p, labrasol were used as oil, co-surfactant and surfactant respectively. The optimized mucoadhesive microemulsion prepared using water titration method was further characterized for particle size, polydispersity index, zeta potential and conductivity measurements followed by drug content, nasal cilio toxicity and biochemical estimation of the selected formulation. Results: All physicochemical parameters conducted, proved that dlx-hcl microemulsion was appropriate for nasal delivery. Chitosan, used as mucoadhesive polymer demonstrated enhanced retention time of the microemulsion in nasal mucosa with no signs of toxicity and epithelial damage. The particle size and zeta potential were found to be of 200 nm and-15 mV respectively considering the formulation safe for nasal delivery. Conclusion: This formulation strategy can be used as an effective targeting technique for the drugs having low bioavailability and poor brain penetration along with an effective method for the treatment long-term disease like depression.